Phytochemical characterization of peanut oil and its ozonized form to explore biological activities in vitro - Aisha M. H. Al-Rajhi; Tarek M. Abdelghany; Samy Selim; Mohammed S. Almuhayawi; Mohammed H. Alruhaili; Mohanned T. Alharbi; Soad K. Al Jaouni (AMB Express)
Abstract Peanut (Arachis hypogaea) is a perennial leguminous crop grown worldwide. This study aims to investigate the chemical composition and pharmaceutical applications of peanut oil using experimental methods for both crude peanut oil and its ozonized form. The peanut oil was exposed to ozone for five hours at flow rates ranging from 0 to 7 L/min to complete the ozonization process. Gas Chromatography-Mass Spectrometry was employed to analyze the chemical composition of peanut oil. The antimicrobial activity of the two oil forms was evaluated against Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumoniae, Salmonella typhi, Candida albicans, and Aspergillus niger. The protein denaturation assay was used to assess anti-inflammatory properties, while the DPPH assay was employed to evaluate antioxidant activity. Cytotoxicity was tested using normal human fibroblast cells (WI-38) and colon cancer cells. The results revealed that exposure to ozone altered the chemical composition of the oil, increasing the number of identifiable molecules from 10 in the crude oil to 29 in the ozonized form. A significant enhancement in the antimicrobial activity of the crude oil was observed after ozonization. Moreover, ozonization notably increased the oil’s antioxidant capacity with IC50 13.06 ± 0.6 µg/mL, while crude oil provide IC50 23.37 ± 0.3 µg/mL compared to IC50 standard ascorbic acid (3.08 ± 0.4 µg/mL) as well as its anticancer (IC50 was 7.31 ± 0.21 and 15.09 ± 0.37 µg/mL against colon carcinoma cells, IC50 was 29.49 ± 2.03 and 24.68 ± 1.44 µg/mL against lung fibroblast normal cells employing crude oil and ozonized oil, respectively) anti-inflammatory potential.